ULTRASTRUCTURAL ANALYSIS OF CHIEF CELLS NUCLEI OF RAT GASTRIC MUCOSA AFTER CO-ADMINISTRATION OF ZOLEDRONIC ACID AND HYDROCORTISONE ACETATE - Кондаурова Г. Ю. (World of Medicine and Biology, 2015)
Studied the effect of zoledronic acid, bisphosphonates relating to the 5th generation, and its combination with hydrocortisone acetate in the different terms of introduction to the structure of the chief cells nuclei of the rats gastric mucosa.Used electron microscopic and morphometric methods of research chief cells of the gastric mucosa.The chief cells were are wrinkled and deformed. The cytoplasm of chief cells vacuolated, slightly stained. Most major cell had enlightened of perinuclear cytoplasm. After 30 days administration of hydrocortisone and zoledronic acid in the nuclei of the chief cells was prevailed heterochromatin, which condensed as near the nuclear membrane and in center of the nucleus.90 days after the administration of drugs in many major chief cells was observed pronounced widening of perinuclear space. Observed nucleoli fragmentation and rings. With increasing duration of the experiment (90 days) in the nuclei of the chief cells there was tendency to increase the heterochromatin area.Electron microscopic study of the chief cells in the body glands in 30 days after drug administration revealed the predominance of functionally inactive cells. In the nuclei of these gland cells heterochromatin is prevailed, its area is increased by 23% (p
Keywords: euchromatin; heterochromatin; apoptosis